SKIPing with teachers: an early years motor skill intervention. (4th May 2017) - Brian, Ali; Goodway, Jacqueline D.; Logan, Jessica A.; Sutherland, Sue
ABSTRACT: Background : Fundamental motor skill (FMS) interventions when delivered by an expert can significantly improve the FMS of young children with and without developmental delays. However, there is a gap in the literature as few early childhood centers employ experts with the professional background to deliver FMS intervention. Purpose : The primary purpose of this study was to investigate the effects of a motor skill program called SKIP (Successful Kinesthetic Instruction for Preschoolers) on student learning of object control skills (OC). A secondary purpose was to examine the extent to which early childhood teachers could implement the SKIP program with fidelity (while receiving on-going coaching and support) and the extent to which instructional fidelity influenced OC improvement in the SKIP condition. Participants and setting : There were two levels of participants in this study, early childhood teachers ( N = 2, Women = 2) and their students ( N = 57; Boys = 53%; M age = 4.39, Range 3–6). All participants were from the same early childhood center located on the campus of a large Midwestern University located in the United States. Data Collection : This study featured a pretest–posttest control group quasi-experimental design. The director of the early childhood center selected the experimental SKIP teachers ( N = 2). Experimental SKIP children ( n = 26) were identified from the classrooms of the experimental SKIP teachers. Teachers implemented SKIP to their students for six weeks (360 minutes of instruction). SKIP teachers' lesson plan fidelity was calculated using a predetermined checklist based upon the lesson plan via digital recordings. Control students ( n = 31) were randomly selected from the remaining six classrooms at the center. Control students received the business as usual condition, which consisted of free play with the availability of the same equipment allocated to the SKIP condition. All students were pretested and posttested using the OC subscale of the Test of Gross Motor Development-2 (TGMD-2) [Ulrich, D. A. 2000. The Test of Gross Motor Development . 2nd ed. Austin: PRO-ED]. Data Analysis : A two-level (students nested within teacher) Hierarchical Linear Model (HLM) examined the extent to which the SKIP intervention improved the OC skills of the students compared to the control group. Lesson plan fidelity was calculated using descriptive statistics. An additional two-level HLM examined the extent to which fidelity of SKIP influenced the OC scores of students in the SKIP condition only. Results : SKIP students significantly improved their OC skills compared to the control students ( p < .001, η 2 = .61). SKIP teachers implemented SKIP with fidelity ( M = 86.5%, SD = .18). Level of fidelity of SKIP significantly influenced students' improvements in OC scores ( p < . 001). Conclusion : SKIP was highly effective in improving the OC skills of the students and SKIP teachers implemented SKIP with fidelity. Greater fidelity positively influenced OC outcomes for students. Further research is warranted to confirm that students' FMS development can be enhanced through FMS intervention with high-quality teaching that is implemented by classroom teachers.